Does Leadership Matter? CEO Leadership Attributes and Profitability Under Conditions of Perceived Environmental Uncertainty - Waldman, David A.; Ramı́rez, Gabriel G.; House, Robert J.; Puranam, Phanish (Academy of Management Journal, 2001)
Using data from 48 Fortune 500 firms, the authors assessed transactional and charismatic CEO leadership as predictors of financial performance. The authors also hypothesized that the relationship between CEO leadership attributes and performance depends on perceived environmental uncertainty, as reported by immediate CEO subordinates. Uncertainty strongly moderated the relationships between performance (measured in later years) and both transactional leadership and charisma. However, the interaction of transactional leadership and uncertainty had no significant effect beyond that of the charisma-uncertainty interaction. Consistent with expectations, charisma predicted performance under conditions of uncertainty but not under conditions of certainty.